The relationship between second-to-fourth digit ratio (2D:4D), muscle strength and body composition to bone mineral density in young women - Arazi, Hamid (Array, 2019)
2D:4D ratio is determined by balance between androgens and estrogens. Low level estrogen reduces bone mineral density (BMD) and incurs negative changes to bone microarchitecture, increasing the risk of osteoporosis and, as a consequence, fracture risk in women. The purpose of this study was to investigate the relationship between 2D:4D, muscle strength and body composition to BMD in young women. One hundred twenty-seven young women (age range 24-36 years) voluntarily participated in this study. Lengths of the second (index) and fourth (ring) fingers, upper and lower body strength and body composition (body mass index, BMI; waist to hip ratio, WHR) and body fat percentage were estimated. Also, blood levels of calcium and 25-hydroxyvitamin D (25OHD) were evaluated and dual-energy X-ray absorptiometry device was used to measure BMD in the lumbar spine (LS) and femoral neck (FN). The results showed that digit ratios, upper body and lower body muscle strength, BMI and fat percentage had a positive relationship with LS and FN BMD (LS BMD: r=.47, r=.56, r=.46, r=.34, r=.28, p≤.001, respectively; FN BMD: r=.34, r=.49, r=.51, r=.45, r=.27, p≤.001, respectively). In addition, there was no significant relationship between WHR and BMD of LS and FN (p˃.05). Multiple linear regression analysis showed the upper body strength was a stronger determinant of LS BMD and the lower body strength was a stronger determinant of FN BMD. Based on the results, the researchers concluded that upper and lower body strength, 2D:4D ratios and BMI were important determinants of young women’s BMD.